2013
DOI: 10.1097/nen.0b013e318293c586
|View full text |Cite
|
Sign up to set email alerts
|

FBXO7 Immunoreactivity in α-Synuclein—Containing Inclusions in Parkinson Disease and Multiple System Atrophy

Abstract: Mutations in the gene encoding the F-box only protein 7 (FBXO7) cause PARK15, an autosomal recessive form of juvenile parkinsonism. Although the brain pathology in PARK15 patients remains unexplored, in vivo imaging displays severe loss of nigrostriatal dopaminergic terminals. Understanding the pathogenesis of PARK15 might therefore illuminate the mechanisms of the selective dopaminergic neuronal degeneration, which could also be important for understanding idiopathic Parkinson disease (PD). The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 16 publications
0
30
1
1
Order By: Relevance
“…The FBXO7 gene encodes an E3 ligase, involved in the ubiquitin‐proteasome pathway of protein degradation, which plays a role in the pathogenesis of neurodegenerative diseases, and pathogenic FBXO7 gene mutations are likely to induce protein dysfunction leading to deficient ubiquitination of substrates. A recent study suggested a role for the FBXO7 protein in the pathogenesis also of common forms of synucleinopathies, such as idiopathic Parkinson's disease (PD) and MSA . In this study, we report on a Turkish family with 2 affected sibs from consanguineous parents carrying a new homozygous p.L34R FBXO7 mutation.…”
mentioning
confidence: 92%
“…The FBXO7 gene encodes an E3 ligase, involved in the ubiquitin‐proteasome pathway of protein degradation, which plays a role in the pathogenesis of neurodegenerative diseases, and pathogenic FBXO7 gene mutations are likely to induce protein dysfunction leading to deficient ubiquitination of substrates. A recent study suggested a role for the FBXO7 protein in the pathogenesis also of common forms of synucleinopathies, such as idiopathic Parkinson's disease (PD) and MSA . In this study, we report on a Turkish family with 2 affected sibs from consanguineous parents carrying a new homozygous p.L34R FBXO7 mutation.…”
mentioning
confidence: 92%
“…Modeling the loss of FBXO7 function in Zebrafish recapitulated cardinal features of the human disease, including loss of dopaminergic neurons and dopamine-dependent locomotor deficit [8]. Last, there is evidence that the FBXO7 protein accumulates in the alpha-synuclein-positive inclusions in the patients with classical late-onset Parkinson's disease and in those with multiple system atrophy, suggesting a broader involvement in the pathogenesis of synucleinopathies [9].…”
Section: Discussionmentioning
confidence: 96%
“…EIF4G1 or DNAJC13 immunoreactivity in Lewy bodies has only been examined in postmortem samples from patients with Parkinson's disease with corresponding gene mutations; less than 50% of Lewy bodies were found to be immunoreactive for DNAJC13 [33] and most were nonimmunoreactive for EIF4G1 [34]. Among the proteins associated with autosomal recessive parkinsonism, parkin, PINK1, DJ-1 (reviewed in [24]), ATP13A2 [35], and FBXO7 [36] have all been reported to localize to Lewy bodies. Glucocerebrosidase, the protein encoded by the GBA gene, was found to be present in an average of 75% of Lewy bodies in patients with GBA mutations and concomitant parkinsonism [37].…”
Section: Lewy Pathology: Lessons From Genetic Forms Of Parkinson's DImentioning
confidence: 97%